THE EFFECT OF MOTIVATION TOWARDS EMPLOYEE PERFORMANCE IN RSUD SUMEDANG - Magistra, Aldilla; Putranto, Nur Arief Rahmatsyah (Journal of Business and Management, 2018)
Abstract.This research aims to improve the employee performance in RSUD Sumedang. The improvement attempt is started by creating motivation workshop and conduct job analysis. The new performance management system is also expected to assist employee to do their job analysis more efficiently. The result of the employee motivation improvement would be a consideration to new performance management system comparing to existing system. From the analysis, it can be concluded that the improved system is able to eliminate the problem and improve employee performance in RSUD Sumedang.Keyword: Motivation, Employee Performance, Human Resource ManagementÂ Â Â